Film cooling of gas turbine blades - Foster, N.W. (1976)
An experimental apparatus was designed and built to study the film cooling effectiveness from a single row of holes at various angles and hole spacings, using a foreign gas technique. Mixtures of Freon 12 and air were injected into an air mainstream to give a range of density ratios encompassing the values found in a gas turbine.